Teaching Profession in Nepal: Attitude and Job Satisfaction of the School Teachers (Far Western Review, 2023)
Quality education is the key factor for overall development of an individual and nation. Quality of education is directly related to competency and dedication of the teacher, as teacher is the main implement or of the educational program. This study investigates the attitude of permanent school teachers towards teaching profession and their level of job satisfaction. Quantitative research design over a sample of randomly selected 200 teachers was used in this study. A Likert type attitude scale was prepared and standardized by the researcher on the sample of 374 school teachers of five districts of Nepal and India but this study is based in context of Nepal. Job satisfaction level was measured by Job Satisfaction Scale (JSST-DM) published by National Psychological Corporation, Agra, India. Normative survey method was used to collect required data. Maslow’s theory of motivation based on the needs hierarchy system was used to interpret the findings of this study. Result was interpreted by using z-score norms based on seven categories, which explored that 20.50 percent of the teachers were favorable towards their profession, 46 percent were unfavorable and 33.50 percent were neutral towards teaching profession. Similarly, percentage of teachers found above Average Satisfied on their job was 37 percent, below Average Satisfied was 40 percent and percent of Average Satisfied teachers was 23. Out of which, nine percent school teachers were extremely satisfied and 13 percent were extremely dissatisfied.Teachers cannot do well on teaching profession unless they have a positive attitude towards their profession and are not satisfied with it. This study reveals that a significant number of teachers are not satisfied with their profession and do not have a positive attitude towards it. It is imperative that the concerned authorities review the policies regarding salary, facilities and position in the national protocol for teachers in order to bring a positive change in the situation.